PENERAPAN PENDEKATAN QUANTUM TEACHING PADA PEMBELAJARAN MATERI HIMPUNAN DI SMP - Nuryanti, Dwi Ria; Mirza, Ade; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research aimed to know the effectiveness implementation of Quantum Teaching approach at SMP. The subject of this research were 31 student at grade VII G SMP Negeri 12 Pontianak. The type of experimental design used in this research were pre-experimental design using one-shot case study as the form of the design. The aspect used to know the efectiviness of learning using a Quantum Teaching approach are the implementation of Quantum Teaching approach, student activities, and student?s learning outcome. Data collection techniques used were measurement and observation.. The data collection tool usedobservation sheet of implementation of Quantum Teaching approach, observation sheet of studen activities, and student learning assessment result. The result obtained were the implementation of Quantum Teaching approach is very good, the activities of student are classified as active, and the classical mastery learning outcomes of students are not achieved. The result that learning using Quantum Teaching approach in the operations of sets at grade VII SMP Negeri 12 Pontianak is said to be ineffective. Keywords: Effectiveness, Quantum Teaching, Sets